Development of a Training Set of Contemporary Salt-Marsh Foraminifera for Late Holocene Sea-Level Reconstructions in southeastern Australia. (30th June 2021) - Williams, Sophie; Garrett, Ed; Moss, Patrick; Bartlett, Rebecca; Gehrels, Roland
We collected contemporary foraminiferal training sets from two salt marshes to enable more precise and accurate proxy historical sea-level reconstructions from southeastern Australia. Combined with an existing training set from Tasmania, this new regional set consists of 112 samples and 16 species of foraminifera, of which 13 are agglutinated. Cluster analyses group the regional training set into a high–elevation cluster, dominated by Trochamminita salsa, a mid–elevation cluster, dominated by Entzia macrescens and Trochammina inflata, and a mid–low elevation cluster dominated by Miliammina fusca and tidal-flat species. We develop transfer functions using local and regional training sets and assess their performance. Our resulting site-specific and chosen regional models are capable of predicting sea level with decimetre-scale precision (95% confidence intervals of 0.12–0.22 m). These results are comparable to other examples from around the world. When developing regional training sets, we advocate that the similarity in the environmental settings (particularly salinity) should be assessed as an alternative way of grouping sites, rather than simply using spatial proximity. We compare our findings with global results and conclude that salt marshes along microtidal coasts yield models with the lowest vertical uncertainties. Studies with the lowest uncertainties are located in the western Pacific and the western Atlantic, whereas those from the eastern Atlantic generally have larger tidal ranges and carry larger vertical uncertainties. Our models expand the existing region available for sea-level reconstruction and can be used to generate new late Holocene sea-level reconstructions across southeastern Australia.